Synthesis, Characterization and Dissolution Behavior of Cupriferous and Nickeliferous Goethites - P. Lussiez (The Minerals, Metals and Materials Society, 1981)
Precipitates consisting of amorphous ferrihydrite and crystalline goethite have been prepared by aging hydrolyzed Fe (III) solutions at room temperature. The precipitates have been characterized by x-ray diffraction and differential thermal analysis. The amorphous ferrihydrite transforms to goethite with time. The ferrihydrite to goethite transformation is affected by the presence of small amounts of copper or nickel coprecipitated with the iron. .The addition of copper decreases the amount of goethite at a given aging time and increases the amount of coprecipitate which is initially dissolved in sulfuric acid, but it does not seem to affect the dissolution of the crystalline part'. It is proposed that adsorption of copper hydroxo species on goethite nuclei delays the ferrihydrite to goethite transformation. The effect of nickel is less dramatic than that of copper. Apparently a portion of the added nickel is adsorbed on the goethite crystallite surface rather than incorporated into the goethite lattice.